New Trends in Internet of Things, Applications, Challenges, and Solutions - Yousra Abdul Alsahib S.aldeen; Kashif Naseer Qureshi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Internet of things (IoT) refers to an innovation and advance field to introduce a new concept of technologies with various potential advantages. In IoT, different types of diverse smart devices and gadgets with smart communication interfaces are connected with each other and offers the plethora of services in our daily life. IoT has gained attention in all fields of life like e-home, e-commerce, e-health, smart grids, intelligent transportation systems, and e-governance. The objects in IoT increasing preponderance of entities and transform objects into new and real-world objects. In this review paper, we discuss the new trend in IoT, its applications and recent challenges and their solutions. In addition, the paper also elaborates the existing systems, IoT architecture and technical aspects with future trends in the field. This review will be helpful to new researchers to find the existing technologies and challenges in order to continue their research in the field.